2022
DOI: 10.1155/2022/5443880
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Nomogram Based on the Triglyceride-Glucose Index to Predict Contrast-Induced Acute Kidney Injury after Percutaneous Intervention in Patients with Acute Coronary Syndrome with Diabetes Mellitus

Abstract: The aim of the study was to investigate the factors influencing contrast-induced acute kidney injury (CI-AKI) after percutaneous intervention (PCI) in patients with acute coronary syndrome (ACS) with diabetes mellitus (DM). A total of 1073 patients with ACS combined with DM who underwent PCI at the Affiliated Hospital of Xuzhou Medical University were included in this study. We divided the patients into the CI-AKI and non-CI-AKI groups according to whether CI-AKI occurred or not. The patients were then randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 46 publications
(50 reference statements)
0
13
0
2
Order By: Relevance
“…Additionally, our results revealed that hyperuricemia constituted a significant risk factor for CIAKI in diabetes. A recent study from China proved that hyperuricemia was associated with CIAKI (OR = 2.363, 95% CI 1.653–3.377, P < 0.001) [ 40 ]. What’s more, it was also shown that patients with uric acid levels above 8.0 mg/dL not only had a greater risk of CIAKI but also an increased risk of hemodialysis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our results revealed that hyperuricemia constituted a significant risk factor for CIAKI in diabetes. A recent study from China proved that hyperuricemia was associated with CIAKI (OR = 2.363, 95% CI 1.653–3.377, P < 0.001) [ 40 ]. What’s more, it was also shown that patients with uric acid levels above 8.0 mg/dL not only had a greater risk of CIAKI but also an increased risk of hemodialysis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that the TyG index could serve as a predictive marker for cardiovascular risk such as coronary artery disease, heart attack, and stroke (9,10,12). In addition, some studies have explored the potential connection between the TyG index and nephropathy, particularly in diabetic nephropathy (13)(14)(15)(16)(17). A higher TyG index, indicative of insulin resistance, can contribute to inflammation, oxidative stress, and vascular dysfunction (9,15,18).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some studies have explored the potential connection between the TyG index and nephropathy, particularly in diabetic nephropathy (13)(14)(15)(16)(17). A higher TyG index, indicative of insulin resistance, can contribute to inflammation, oxidative stress, and vascular dysfunction (9,15,18). In addition, the TyG index exhibits a positive correlation with a high risk of developing diabetic nephropathy and other renalrelated complications (15,17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The score established by Mehran et al was widely used in clinics[8,9]. In recent years, due to the advent of big data, many models have been built based on machine learning methods [10][11][12]. However, there are still some challenges in the application of these models.…”
mentioning
confidence: 99%